Resiliensi pada Janda Cerai Mati - Gayatri, Fitriana Ery, Aad Satria Permadi, S.Psi, MA (2016)
Resilience in divorced woman died is the ability that was found in ourselves a divorced woman dead to rise from adversity experienced because her husband who die so that it can be daily living with her children.Resilience no appears with itself, but the motivation from the and off the these individuals to keep survive.The status of being a widow not an easy thing to be acceptable to someone, let alone a widow that husbands who die. But indirectly, divorced woman dead are required to could still facing in positive over the difference life before and after a widow, able to perform the problem solving exactly, maintaining good relations with others, to fulfill the needs himself and his sons and optimistic see their future who want to was without any the figure of husband in his life. The purpose of this research is to assess and described the dynamics of resilience in divorced woman dead.Informants this research as many as six one who, which were selected purposively sampling with characteristicsdivorced woman dead aged 40 to 50 years (middle age) and have a job. This research uses the interview and observation as the supporting data. The result of this research is divorced woman dead originally experienced lonely and loss over lost your husband who died the world because of illness or the death of a sudden.Potential resilience formed the presence of attitude of the problems faced by after a widow, hope to survival, a creed against power allah as well as the capability yourself and social interaction.And the factors that affect individual to resiliensi i.e. able to motivate self, tawakal, proximity to family, habits, orang-outang self, the future yourself, the front of the kids, confident, care and social relationships that good. Keywords: Resilience, Divorced Woman Died, Middle Age